CRIMINAL RESPONSIBILITY FOR LAND CRIME PRACTICES CONCERNING ISSUANCE OF OVERLAPPING LAND CERTIFICATES BY THE NATIONAL LAND AGENCY - I Made Muliartha; I Gede Susila Guna Yasa (UNES Law Review, 2023)
Current land crime practices that need to be understood and straightened out are related to the problem of multiple certificates that occur and are often experienced by people who have multiple certificates, so far the problem of overlapping certificates of ownership of land is being questioned as a civil matter even though every action and individual official The National Land Agency, in carrying out its duties, must reasonably be suspected of an unscrupulous National Land Agency official who deliberately issued a certificate even though the certificate had previously been issued. Even though in the case of the issuance of overlapping certificates, why is it still happening so often, this is because the practice of land crimes is high which has led to the practice of bribery against officials of the National Land Agency who often do not want their positions and positions to be criminally investigated so they use the pretext of overlapping certificates. This was a technical error made by surveyors and officials in collecting physical and juridical data related to the land so that in the future problems arose between the party that previously had a certificate of ownership rights and the party that had just been issued by the National Land Agency.